Hitting the sweet spot: Exploiting HIV-1 glycan shield for induction of broadly neutralizing antibodies - Wagh, Kshitij (Curr Opin HIV AIDS, 2020)
PURPOSE OF REVIEW: The surface of the HIV-1 Env glycoprotein, the target of neutralizing antibodies, is extensively covered by N-linked glycans that create a glycan shield. Broadly neutralizing antibodies (bNAbs), the primary targets of HIV-1 vaccine design, have to negotiate this glycan shield. Here, we review the barriers and opportunities that the HIV-1 glycan shield presents for vaccine induction of bNAbs. RECENT FINDINGS: Glycan shields can impact the nature of the antibody response and influence the development of neutralization breadth in HIV-1 infections. The architecture of the glycan shield arising from glycan interactions and dynamics have been modeled, and its fine structure, i.e. the site-wise glycan heterogeneity, have been determined for some isolates. While the extent of glycan shielding is conserved, the precise number, location, and processing of glycans, however, is strain dependent. New insights continue to reveal how such differences can impact bNAb activity and development. Novel approaches have exploited the glycan shield for designing immunogens that bind the germline precursors of bNAbs, a critical roadblock for vaccine-induction of bNAbs. SUMMARY: The HIV-1 glycan shield can significantly impact the induction and maturation of bNAbs, and a better understanding of how to manipulate it will improve immunogen design.